MAGNETO-OPTIC STUDY OF CHROMIUM DOPED BI12SIO20: MAGNETO-OPTIC STUDY OF CHROMIUM DOPED BI12SIO20 - Petkova, Petya; Vasilev, Petko; Ismail, I. (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Faraday rotation in Bi12SiO20:Cr (BSO:Cr) has been investigated on (100) direction at room temperature using refractive index data in the spectral region 700 – 850 nm. Verdet constant (V) spectrum is determined in the same spectral region for this crystal. The Verdet constant spectrum of pure BSO can be described by the linear dependence V-1 (λ 2) (λ is the wavelength of the light). The Cr-ions in the sillenite crystal lattice cause a deviation of Verdet constant from the mentioned linear dependence in the spectral region of the absorption impurity structure. The magneto-optic anomaly factor γ is also investigated.